MO095THE FECAL ABUNDANCE OF SHORT CHAIN FATTY ACIDS IS INCREASED IN MEN WITH A NON-DIPPING BLOOD PRESSURE PROFILE. (29th May 2021) - Huart, Justine; Cirillo, Arianna; Saint-Remy, Annie; Krzesinski, Jean-Marie; De Tullio, Pascal; Jouret, François
Abstract: Background and Aims: Gut microbiota (GM) has been involved in the pathophysiology of hypertension (HT), possibly via its role in the production of short chain fatty acids (SCFAs) from diet carbohydrate fermentation. The absence of a significant drop in night-time BP (also known as the non-dipping BP profile) measured by 24-hour ambulatory BP monitoring (24h-ABPM) has been associated with poor renal and cardiovascular outcomes, independently of HT. The putative link between GM-derived metabolites and BP dipping status is still unknown. Method: We investigated a cohort of male volunteers who were prospectively recruited and subjected to 24h-ABPM, stool sample collection and a medical questionnaire. A patient was categorized as non-dipper if the ratio between night and day systolic BP was >0.9. The patients were categorized in two groups, i.e. NT or HT, on the basis of the European Society of Hypertension criteria. Metabolomics analyses were conducted using Nuclear Magnetic Resonance. Fecal concentrations of acetate, butyrate and propionate were obtained by integrating the signals at 1.93 ppm, 1.56 ppm and 1.05 ppm, respectively. Mann-Whitney test and Chi-square test were used to compare continuous and categorical variables, respectively. Results: Our 44-case cohort included 13 non-dippers (29.6%) and 31 dippers, with 35 HT (79.4%) and 9 NT patients. Ten non-dippers (28.6%) and 25 dippers were HT. Nineteen HT patients were under anti-hypertensive medications (43.1%), including 7 non-dippers and 12 dippers. The mean age and body mass index (BMI) of the cohort were 50.8±9.5 years and 26.3±3.5 kg/m², respectively. No significant difference in age, BMI, smoking habits, alcohol consumption, familial HT, personal history of diabetes, cardiovascular or gastro-intestinal disorders was observed between dippers and non-dippers. The relative quantification of fecal SCFAs showed higher amounts of acetate, butyrate and propionate in the stools of non-dippers versus dippers (p=0.0252, p=0.0468, and p=0.0496, respectively; n=44 in toto) (Figure 1A ). Similarly, the fecal amounts of acetate, butyrate and propionate were higher in non-dippers versus dippers in patients without anti-hypertensive medications (p=0.0414, p=0.0108, and p=0.0602, respectively; n=25 in toto) (Figure 1B ). When focusing only on HT patients without any anti-hypertensive medications, a not significant trend for higher amounts of the 3 main SCFAs was still found in the stools of non-dippers versus dippers (p=0.0556; n=16 in toto). Conclusion: Our pilot study highlights a putative link between GM-derived SCFAs and the BP dipping status, despite the BP status itself or the anti-hypertensive medications. No significant confounding factors were found between dippers and non-dippers in our cohort. The non-dipping BP profile is thought to reflect the disruption of the circadian BP rhythm. A circadian misalignment between peripheral and central clocks has also been described in the GM of jetlagged animals and patients, which may in turn perturb the rhythmic secretion of metabolites. One may thus speculate that the non-dipping BP profile may be linked to an altered homeostasis of GM-derived SCFAs. Although confirmatory data in larger cohorts are required, our original observations unravel innovative pathophysiological pathways in the field of the circadian regulation of BP levels.